Comparison of Selected National Approaches to Crisis Management Authorities ‘Exercises - Katerina GOGHOVA (Communications of International Proceedings, 2022)
One of the key means of crisis management is an exercise used to test the functionality and feasibility of approved standards and procedures as well as the skills and training of crisis management authorities and Integrated Rescue Service components. The article provides a comparison of foreign approaches to the crisis management authorities ‘exercise at the national level. The aim is to characterize and compare approaches to crisis preparedness through exercise and its individual phases - preparation, implementation and evaluation of the exercise - for selected countries (the Czech Republic, United States of America, Denmark, Sweden and the Netherlands). The results of the comparative analysis will be used to complement and improve the individual phases of the exercise in the Czech Republic. The comparative analysis shows that the most sophisticated system of the crisis management authorities ‘exercise is carried out in the United States of America and Sweden.
Keywords: exercise; crisis management authorities; crisis management; exercise evaluation